Medicare Prescription Plans Limit Access to Recommended Drugs for Clostridioides difficile Infection. (9th October 2021) - Buehrle, Deanna; Clancy, Cornelius J
Abstract: We analyzed June 2021 Medicare Advantage/Part D enrollment and formulary data. Oral vancomycin and fidaxomicin, frontline Clostridioides difficile treatments, were in the formulary for 100% (42314676 of 42314676) and 84.1% (35598385 of 42314676) of enrollees, respectively. However, they were broadly accessible (formulary, unrestricted, tier 1 or 2) to only 14.4% (6104348 of 42314676) and 1.1% (483004 of 42314676), respectively.